1997
DOI: 10.1021/cm970004b
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent Al3+ Ion Conduction in Aluminum Tungstate Solid

Abstract: Ionic conduction of trivalent aluminum in solid aluminum tungstate, Al 2 (WO 4 ) 3 , has been directly and quantitatively demonstrated. Trivalent ions, especially for aluminum where the polarizability is considerably low, are strongly bonded in a crystal lattice and have been believed to be unlikely to exhibit migration in solids because of high electrostatic interaction with the surrounding skeleton structure. The material, Al 2 (WO 4 ) 3 , which has the Sc 2 (WO 4 ) 3 structure, was selected in order to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 19 publications
8
86
2
1
Order By: Relevance
“…During this study, we noticed that Al 2 (WO 3 ) 4 had an intrinsic electrical conductivity of nearly 4 × 10 −6 S cm −1 at 600 • C; however, its conductivity was not high at room temperature. 14 We found that the liquid electrolyte had penetrated the solid electrolyte region (the space between the ceramic particles), reaching the electrode. It was thus considered possible to fabricate a rechargeable aluminum-air battery with an insulating material, such as aluminum oxide, in order to replace the solid electrolyte.…”
mentioning
confidence: 83%
“…During this study, we noticed that Al 2 (WO 3 ) 4 had an intrinsic electrical conductivity of nearly 4 × 10 −6 S cm −1 at 600 • C; however, its conductivity was not high at room temperature. 14 We found that the liquid electrolyte had penetrated the solid electrolyte region (the space between the ceramic particles), reaching the electrode. It was thus considered possible to fabricate a rechargeable aluminum-air battery with an insulating material, such as aluminum oxide, in order to replace the solid electrolyte.…”
mentioning
confidence: 83%
“…[6] Treatment of FeCl 2 with C 5 Me 5 Li and then 2-chloro-4-methyl-7H-cyclopenta[b]pyridinyllithium affords ferrocene derivative 2. [7] Kumada coupling of 2 with MeMgBr furnishes 3, which is lithiated and then quenched with ClPPh 2 to provide ligand 1, the enantiomers of which are readily resolved by chiral HPLC. We have determined the absolute configuration of (À)-1 by X-ray crystallography.…”
Section: ) Hydrolysismentioning
confidence: 99%
“…Among the ion species conducting in solids, monovalent and divalent cations and anions are well known to migrate in solids. In 1995 [3], macro-scopic trivalent cation conduction is solids was demonstrated by us and after that, various trivalent cations such as A13+ [4] and rare earth cations [5][6][7], are proved to migrate in solids in such structures as Sc2(WO4)3 type [8] and NASICON type. Among various trivalent cations, A13+ is one of the most practically applicable cation species, and especially, (A10.2Zr0.8)20/19Nb(PO4)3 of the NASICON type [9], has been demonstrated to show as high ion conductivity as yttria stabilized zirconia (YSZ) [10] and calcia stabilized zirconia (CSZ) [10].…”
Section: Introductionmentioning
confidence: 99%